2013
DOI: 10.1155/2013/978087
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Central Precocious Puberty Associated with 11 MbDe NovoDistal Deletion of the Chromosome 9 Short Arm

Abstract: We report a girl with a de novo distal deletion of 9p affected by idiopathic central precocious puberty and intellectual disability. Genome-wide array-CGH revealed a terminal deletion of about 11 Mb, allowing to define her karyotype as 46; XX, del(9)(p23-pter). To our knowledge, this is the second reported case of precocious puberty associated with 9p distal deletion. A third case associates precocious puberty with a more proximal 9p deletion del(9)(p12p13,3). In our case, more than 40 genes were encompassed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Such associations were found in this study for patients with Silver-Russell and Temple syndromes (maternal uniparental disomy of chromosome 7 and paternal imprinted disruption or maternal uniparental disomy on chromosome 14, respectively) (42), Williams-Beuren syndrome (7q11.23 microdeletion) (17) and Kabuki syndrome (MLL2 gene mutation) (18). In other chromosomal abnormalities, incidental association could not be excluded, but rare clinical cases have already been reported (15,16,43).…”
Section: Discussionsupporting
confidence: 50%
“…Such associations were found in this study for patients with Silver-Russell and Temple syndromes (maternal uniparental disomy of chromosome 7 and paternal imprinted disruption or maternal uniparental disomy on chromosome 14, respectively) (42), Williams-Beuren syndrome (7q11.23 microdeletion) (17) and Kabuki syndrome (MLL2 gene mutation) (18). In other chromosomal abnormalities, incidental association could not be excluded, but rare clinical cases have already been reported (15,16,43).…”
Section: Discussionsupporting
confidence: 50%
“…Distinct chromosomal abnormalities have been associated with complex syndromic phenotypes, including CPP, such as 1p36 deletion [45], 1q11.23 microdeletion (Williams-Beuren syndrome) [46], 9p deletion [47], and maternal uniparental disomy of chromosomes 7 (Silver-Russell syndrome) and 14 (Temple syndrome) [34,48]. Interestingly, chromosome 7 and 14 maternal uniparental disomies are genomic imprinting disorders like the Prader-Willi syndrome.…”
Section: Potential Imprinting Defects In Cppmentioning
confidence: 99%
“…Chromosomal abnormalities were found in 4 patients (among 8 evaluated) of 25 (16%) of the present series: chromosome duplication of 11, 15 ( n = 2) and 17. Cases of precocious or early puberty associated with chromosomal abnormalities have been reported (Table 3): deletion (2325) or duplication (28) of 9p, deletion of 1p36 (26), 46,XX/69XXX mixoploidy (27), triple X syndrome (28), duplication or inversion duplication of 15 (29), or maternal uniparental disomy for chromosome 14 (30). These data suggested that performing a karyotype analysis should be recommended for patients with precocious or early puberty and associated disorders without any obvious etiology (primarily tumor or neurofibromatosis).…”
Section: Discussionmentioning
confidence: 99%